A German multicenter real-world analysis of talquetamab in 138 patients with relapsed/refractory multiple myeloma - Frenking, Jan; Riedhammer, Christine; Teipel, Raphael; Bassermann, Florian; Besemer, Britta; Bewarder, Moritz; Braune, Jan; Brioli, Annamaria; Brunner, Franziska; Dampmann, Maria; Fenk, Roland; Gezer, Deniz N.; et al. (HemaSphere, 2025)
Bispecific T-cell engagers (BTCEs) represent a paradigm shift in the treatment of relapsed/refractory multiple myeloma (RRMM). Talquetamab, a GPRC5DxCD3 BTCE, has shown promising results in the MonumenTAL-1 trial and was recently approved by the Food and Drug Administration and the European Medicines Agency. However, treatment under real-world conditions may not represent patient characteristics in clinical trials with restricted enrollment criteria. We performed a retrospective real-world analysis including 138 RRMM patients treated with talquetamab at 21 German centers. Of evaluable patients, 43% had ISS stage III, 37% had extraosseous disease, and 48% had high-risk cytogenetics. After a median of six prior therapy lines, 58% of patients would not have been eligible for MonumenTAL-1. With a median follow-up of 8.2 months, we observed an overall response rate of 65% and a median progression-free survival of 6.4 months (95% confidence interval 5.1-9.0). Prior BTCE exposure, ISS stage III, extraosseous disease, and penta-drug refractory disease were associated with unfavorable outcomes. Grade ≥ 3 cytokine release syndrome and neurotoxicity occurred in 5.1% and 1.5% of patients, respectively. In summary, our real-world study confirms the efficacy and safety of talquetamab, despite a high proportion of patient- and disease-related risk factors. These results support its use as bridging or long-term treatment, even in advanced stages.